INCIDENCE AND DISTRIBUTION OF VIRUSES INFECTING CASSAVA IN KADUNA AND SOKOTO STATES, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
Field survey was conducted in the 2015 wet season to determine the incidence and distribution of cassava viruses in Kaduna and Sokoto States, Nigeria. Eighteen farms from 3 Local Government Areas namely; Lere, Chikun and Kajuru (Kaduna State) and Tureta, Shagari and Tambuwal (Sokoto State) were surveyed. Symptomatic leaves (180) and asymptomatic leaves (90) were collected from the surveyed farms. Enzyme Linked Immosorbent Assay (ELISA) technique was used to test the presence of viruses infecting cassava. Three viruses: African cassava mosaic virus (ACMV), East African cassava mosaic virus (EACMV) and Cassava Congo sequivirus (no acronyms) were detected. Triple Antibody Sandwich (TAS- ELISA) was used to detect ACMV and EACMV while Double Antibody Sandwich (DAS- ELISA) was used to detect Cassava Congo sequivirus. ACMV had the highest incidence and was widely spread, the highest incidence was recorded in Lere Local Government (68.9%) and least was Tambuwal LG (11.0), followed by EACMV with highest incidence in Tambuwal (22.23%) and no occurrence in Kajuru. Cassava Congo sequivirus recorded the highest incidence in Kajuru (43.33%). Mixed infections occur in some of the farms. This the first report of Cassava Congo sequivirus in Nigeria and Africa. Wide spread occurrence of ACMV calls for effective management of the virus.
Keywords: Viruses; occurrence; cassava and survey